SIKAP EKSKLUSIVISME PENGANUT KEPERCAYAAN LOKAL PEMENA DALAM ANALISIS KEKERASAN SIMBOLIK DI DESA KIDUPEN KABUPATEN KARO - Andriansyah, Dedi; Sinaga, Wahyuni; Tarigan, Lisbhet Same Lady; Sembiring, Yenni Br; Depari, Sari Sesilia (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2023)
This research aims to explore the exclusivism of local Pemena adherents. Pemena's local beliefs can be classified as animism, namely belief and belief in ancestral spirits. The results of the research show data related to the background of the exclusivism attitudes of Pemena adherents, forms of exclusivism, symbols of violence faced by Pemena adherents, and strategies for maintaining local Pemena beliefs. This research uses a qualitative method with a Spradley ethnographic approach, this aims to describe the current (ethnographic) picture of the religious life of local Pemena beliefs in Kidupen Village. The background to the exclusivism attitude of Pemena adherents is inseparable from symbolic violence in the form of stigmatization of being considered devil worshipers (begu). This situation has been going on since the New Order until now and has had the impact of the discriminatory treatment they have experienced.